Smart choices : a practical guide to making better decisions - Hammond, John S., 1937-; Keeney, Ralph L., 1944-; Raiffa, Howard, 1924-2016. (Boston, Mass. : Harvard Business School Press, 1999)
Offers readers an easy-to-follow process to improve ways to make business decisions, family decisions, and personal decisions.
Making smart choices: how to think about your whole decision problem: a proactive approach -- Problem: how to define your decision problem to solve the right problem -- Objectives: how to clarify what you're really trying to achieve with your decision -- Alternatives: how to make smarter choices by creating better alternatives to choose from -- Consequences: how to describe how well each alternative meets your objectives -- Tradeoffs: how to make tough compromises when you can't achieve all your objectives at once -- Uncertainty: how to think about and act on uncertainties affecting your decision -- Risk tolerance: how to account for your appetite for risk -- Linked decisions: how to plan ahead by effectively coordinating current and future decisions -- Psychological traps: how to avoid some of the tricks your mind can play on you when you're deciding -- The wise decision maker: how to make smart choices a way of life.
Includes bibliographical references and index.
Print version record.
Keywords: Decision making; Decision Making; Prise de décision; decision making; SELF-HELP -- Motivational & Inspirational; Prise de décision; Decision making; Führungskraft; Entscheidungsfindung; Besliskunde; Prise de décision